Microstructures, Mineral Chemistry And Oxygen Isotopes Of Two Adjacent Mylonite Zones: A Comparative Study - Timothy E. LaTour; Robert Kerrich (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1982)
Microstructures and mineral chemistry of amphiboles and plagioclases from two spatially related mylonite zones at the Grenville front are significantly different, suggesting different physical conditions (including temperature) for the formation of the two zones. Oxygen isotopes indicate multiple episodes of fluid-rock interaction, consistent with previously determined mylonitization temperatures and postulated tectonic evolution of the area.